+0  
 
0
296
2
avatar

sinh^-1 (1)

Guest Sep 14, 2017
 #1
avatar+7449 
0

sinh^-1 (1)

 

\(sinh^{-1}(1°)_{deg}=asinh(1°)_{deg}\color{blue}=50.498986710526\\ sinh^{-1}(1)_{rad}=asinh(1)_{rad}\color{blue}=0.88137358702\)

 

laugh  !

asinus  Sep 14, 2017
edited by asinus  Sep 14, 2017
 #2
avatar+20009 
0

hyperbolic functions

\(sinh^{-1} (1)\)

 

Formula:

\(\begin{array}{|rcll|} \hline sinh(z) &=& \frac{e^z-e^{-z}}{2} \\ z &=& sinh^{-1} (\frac{e^z-e^{-z}}{2} ) \\ \hline \end{array}\)

 

\(z=\ ?\)

\(\begin{array}{|rcll|} \hline \frac{e^z-e^{-z}}{2} &=& 1 \\ e^z-e^{-z} &=& 2 \\ e^z-\frac{1}{e^{z}} &=& 2 \quad & | \quad \text{substitute } e^z = x \\ x-\frac{1}{x} &=& 2 \quad & | \quad \cdot x \\ x^2-1 &=& 2x \\ x^2-2x-1 &=& 0 \\\\ x &=& \frac{2\pm \sqrt{4-4\cdot(-1)} }{2} \\ &=& \frac{2\pm \sqrt{8} }{2} \\ &=& \frac{2\pm \sqrt{2\cdot 4 } }{2} \\ &=& \frac{2\pm 2\sqrt{2} }{2} \\ \mathbf{x} &\mathbf{=}& \mathbf{1\pm \sqrt{2}} \quad & | \quad x = e^z \\ e^z & = & 1\pm \sqrt{2} \quad & | \quad \ln() \\ z & =& \ln(1\pm \sqrt{2}) \\\\ z_1 &=& \ln(1 + \sqrt{2}) \\ z_2 &=& \ln(1 - \sqrt{2}) \quad & | \quad \text{no solution } \quad 1 - \sqrt{2} < 0! \\\\ \mathbf{sinh^{-1} (1)= z} &\mathbf{=}& \mathbf{\ln(1 + \sqrt{2})} \\ \mathbf{sinh^{-1} (1) } &\mathbf{=}& \mathbf{0.88137358702\ldots} \\ \hline \end{array}\)

 

laugh

heureka  Sep 14, 2017

24 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.